Enhanced Photocatalytic Performance of Ag-Modified ZnO for the Degradation of Tartrazine Dye - Thi, Cam Vi Dao; Nguyen, Tuan Anh; Pham, Quang Minh; Vu, Anh-Tuan (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
In this study, ZnO materials were synthesized using the hydrothermal method, and then modified with Ag using glucose, a biologically derived and environmentally friendly reducing agent, to produce Ag/ZnO materials with varying Ag contents. The obtained material samples were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), and photoluminescence spectroscopy (PL) to determine the crystal structure, surface morphology, and optical properties, respectively. The results showed that the Ag/ZnO sample containing 5 % Ag (Ag/ZnO-5 %) was able to completely decompose Tartrazine (TA) dye after 80 min of irradiation with an 85 W UV lamp, with a first-order reaction rate constant k = 0.03789 min-1 and degradation capacity of 20 mg/g. In comparison, pure ZnO achieved an efficiency of less than 60 %. Factors affecting the photodegradation efficiency, such as initial TA concentration, catalyst dosage, and pH of the solution, were investigated to optimize the reaction conditions. In addition, the Ag/ZnO material exhibited high degradation efficiency toward various organic pollutants, such as Janus Green B (JGB), Congo red (C-Red), Methylene blue (MB), and Caffeine, indicating its potential for broad applications in wastewater treatment. Notably, the investigation of different irradiation light sources (UV, visible light, and sunlight) revealed that sunlight could promote complete degradation of TA in only 20 min of exposure. The photocatalytic reaction mechanism was also proposed to clarify the role of Ag as well as ZnO in enhancing the performance of the Ag/ZnO material system. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).